Hyaluronan polymeric micelles for topical drug delivery - Šmejkalová, Daniela; Muthný, Tomáš; Nešporová, Kristina; Hermannová, Martina; Achbergerová, Eva; Huerta-Angeles, Gloria; Svoboda, Marek; Čepa, Martin; Machalová, Veronika; Luptáková, Dominika; Velebný, Vladimír (Carbohydrate polymers, 2017)
Nanosized materials offer promising strategy for topical drug delivery due to their enhancing effect on drug percutaneous transport across the stratum corneum barrier. In this work, polymeric micelles made from hydrophobized hyaluronic acid (HA) were probed for skin delivery. Compared to non-polymeric micelle solutions containing similar drug amount, in vitro skin penetration analysis indicated 3 times larger deposition of drug in the epidermis and 6 times larger drug deposition in the dermis after 5h of topical treatment in Franz diffusion cells. The drug deposition was further increased with prolonged time of topical treatment. Laser confocal microscopy revealed the accumulation of both, the HA forming the vehicle and the payload, in the epidermis and dermis. Although fluorescent labeling of the HA would suggest co-transport of the HA and the drug, loading FRET pair dyes in the micellar core clearly demonstrated gradual micelle disruption with increasing skin depth. Transcellular penetration was the predominant pathway for the loaded drug. The HA polymeric micelles also demonstrated increased bioactivity of loaded compound in vitro and in vivo. In addition, the loaded micelles were found to be stable in cream formulations and thus they have great potential for topical applications for cosmetic and pharmaceutical purposes.
Keywords: micely; techniky in vitro; Humans; Skin penetration; lidé středního věku; kožní absorpce; Drug Carriers; dospělí; lidé; Micelles; zvířata; Drug Liberation; Hyaluronan; uvolňování léčiv; Polymeric micelle; Swine; buněčné linie; polymery; Skin Cream; Adult; Polymers; Cell Line; pleťový krém; Middle Aged; kyselina hyaluronová; Skin Absorption; nosiče léků; In Vitro Techniques; Animals; Hyaluronic Acid; prasata